SWOT IMPLEMENTATION IN HYBRID MARKETING STATEGY AT PERUMDA PUSPAHASTAMA, PURBALINGGA CENTRAL JAVA - suwali suwali; Vicktor Bintang Panunggul; Ayu Sitanini; Faizah Noviani (Universitas Perjuangan Tasikmalaya, 2023)
Rice is a basic need for the world community, especially in Indonesia. PERUMDA Puspahastama is a company located in Purbalingga Regency engaged in trade, especially rice. The marketing strategy used by Puspahastama so far has used hybrid (online and offline). This study uses a qualitative method with observation and descriptive analysis with SWOT. The data were taken from interviews with the chairman of PERUMDA Puspahastama. The results of the study found that hybrid marketing strategies influenced sales results. Each of these deficiencies can be overcome with these two strategies. Keywords: Marketing Strategy, SWOT, Puspahastama, Rice